3PG model to estimate the productivity, Carbon storage and Aridity Index of Eucalyptus L'Hér. forest plantations in Mexico - Hakamada, Rodrigo; Coronado, Jesús Prados; Falcão, Cassiano José Lages Marinho [UNESP]; Carrero, Omar; Sulbarán-Rangel, Belkis (Revista Mexicana de Ciencias Forestales, 2025)
One of the most efficient ways to mitigate climate change is through the sequestration and storage of carbon through forest plantations, which, in addition to storing it, can generate a change in the soil water balance; therefore, the two parameters, evaluated together, generate valuable information. The objective of this work was to estimate carbon storage and the Aridity Index (evapotranspiration/precipitation) utilizing ecophysiological modeling (3PG model) for eucalyptus plantations in Mexico, and the main factors influencing evapotranspiration and Carbon storage were identified. From a practical point of view, maps were drawn showing the suitability of the land for eucalyptus plantations. The estimated average achievable productivity was 55 m3 ha-1 yr-1, with a variation of 18 to 117 m3 ha-1 yr-1; while, the above-ground Carbon storage was 26 to 288 t ha-1 at six years, with an average of 80 t ha-1. Evapotranspiration ranged from 426 to 1 713 mm yr-1 (average 1 053 mm yr-1), which resulted in an Aridity Index of 0.61 to 8.87. The main variables controlling productivity, Carbon stock, and the Aridity Index in Mexico are precipitation and latitude. The suitability maps for eucalyptus plantations in Mexico showed areas of high and very high suitability totaling 1.4 million hectares, confirming the country's enormous potential for developing eucalyptus plantations.
Modelo 3PG para estimar la productividad, almacenamiento de Carbono e Índice de Aridez en plantaciones forestales de Eucalyptus L'Hér. en México
Keywords: ecophysiological model; Mean Annual Increment; process-based modeling; productivity; Suitability for plantations; water balance